Pengaruh Locus Of Control Dan Motivasi Terhadap Kinerja Individu Pada PT. Nusa Halmahera Minerals - Brenda H. Bawanda; Riane J. Pio; Wehelmina Rumawas (Universitas Sam Ratulangi, 2018)
The background of this research is PT Nusa Halmahera Minerals where the author will examine the extent of the relationship between Locus Of Control and Motivation to Performance of Individuals within the scope of Human resources. The purpose of this study was to find out and obtain a review of the influence of locus of control, while Motivation is an urge in a person to be able to do what he wants to do, but motivation is followed by a will while individual performance ishow good or qualified employees are in carrying out their responsibilities or you can also say the work done by the employee. The author takes the locus of control research title because the LOC is divided into two parts, namely the external LOC and internal LOC and Motivation as a measure to see whether a strong or weak relationship between variables. this is a quantitative descriptive study with a sample of 100 respondents obtained by using probability sampling method withproportionale sampling method using 1-5 Likert scale measuring instruments. to test the effect of the quality used by the instrument, test validity and reliability, while the data were analyzed using multiple linear regression method with t test and coefficient of determination (multiple correlation). therefore, H1 and H2 are rejected, which means that simultaneously the independent variables (locus of control and motivation) have a positive effect on the dependent variable individualperformance) but are very weak or small in relation between the two. The results of the coefficient of determination show that the adjusted R square rate is -0.018 or 01.8%, which means that variations in individual performance can be explained by locus of control and motivation, while the remaining 98.2% can be explained by other variables outside the research variable.Key Words: Locus Of Control, Motivation, Individual Performance.